Whole-Genome Sequencing of Brachyspira hyodysenteriae Isolates From England and Wales Reveals Similarities to European Isolates and Mutations Associated With Reduced Sensitivity to Antimicrobials - Stubberfield, Emma; Sheldon, Jonathan; Card, Roderick M.; AbuOun, Manal; Rogers, Jon; Williamson, Susanna; Kay, Gemma L.; Pallen, Mark J.; Anjum, Muna F. (Frontiers in Microbiology, 2021)
Brachyspira hyodysenteriae is the principal cause of swine dysentery, a disease that threatens economic productivity of pigs in many countries as it can spread readily within and between farms, and only a small number of antimicrobials are authorised for treatment of pigs. In this study, we performed whole-genome sequencing (WGS) of 81 B. hyodysenteriae archived at the Animal and Plant Health Agency (APHA) from diagnostic submissions and herd monitoring in England and Wales between 2004 and 2015. The resulting genome sequences were analysed alongside 34 genomes we previously published. Multi-locus sequence typing (MLST) showed a diverse population with 32 sequence types (STs) among the 115 APHA isolates, 25 of them identified only in England; while also confirming that the dominant European clonal complexes, CC8 and CC52, were common in the UK. A core-genome SNP tree typically clustered the isolates by ST, with isolates from some STs detected only within a specific region in England, although others were more widespread, suggesting transmission between different regions. Also, some STs were more conserved in their core genome than others, despite these isolates being from different holdings, regions and years. Minimum inhibitory concentrations to commonly used antimicrobials (Tiamulin, Valnemulin, Doxycycline, Lincomycin, Tylosin, Tylvalosin) were determined for 82 of the genome-sequenced isolates; genomic analysis revealed mutations generally correlated well with the corresponding resistance phenotype. There was a major swine dysentery intervention program in 2009-2010, and antimicrobial survival curves showed a significant reduction in sensitivity to tiamulin and valnemulin in isolates collected in and after 2010, compared to earlier isolates. This correlated with a significant increase in post-2009 isolates harbouring the pleuromutilin resistance gene tva(A), which if present, may facilitate higher levels of resistance. The reduction in susceptibility of Brachyspira from diagnostic submissions to pleuromutilins, emphasises the need for prudent treatment, control and eradication strategies.